Peningkatan Pengetahuan Tentang Strategy Digital Marketing Hospital Transformation Tim Pemasaran Rumah Sakit Umi Barokah Boyolali - Hesty Latifa Noor; Anton Susanto; Kinanti Anggraini; Stevina Sophia Chrisnanda (PPNI UNIMMAN, 2024)
Umi Barokah Boyolali Hospital is a private hospital with type D which is one of the private hospitals formed to provide services to the community in the form of services that prioritize service in carrying out its activities based on customer satisfaction. Umi Barokah Boyolali Hospital is currently developing to offer health services with target service coverage in Boyolali Regency. Currently, the marketing team at Umi Barokah Boyolali Hospital is starting to develop marketing efforts which are expected to increase patient visits. High competition between hospitals is one of the factors that patient visits at Umi Barokah Boyolali Hospital tend to fluctuate. The marketing team's lack of knowledge regarding Digital Marketing, the large number of job desks for each marketing team member and the lack of supporting equipment result in digital marketing efforts being less than optimal. The marketing strategy that is currently being implemented is still not optimal considering that views on various social media for hospitals are still lacking. The solutions offered through this Community Service activity are (1) Providing education regarding the Digital Marketing Hospital Transformation Strategy (2) Providing education regarding the Digital Marketing Hospital Transformation Strategy method which can be applied in hospitals (3) Training on the Digital Marketing Hospital Transformation Strategy which combines Media Content Marketing, Collaboration Transformation, Expanding Social Media Networks, Optimizing Patient Services through digital marketing. The methods used in this community service include: (1) Increasing the marketing team's knowledge regarding the Digital Marketing Hospital Transformation Strategy to increase the number of patient visits; (2) Increasing the skills of the marketing team in implementing the Digital Marketing Hospital Transformation Strategy (3) Increasing and developing strategies to produce user interfaces for collecting customer data (4) Mentoring. The outputs of this activity are (1) Publication of service results in the Community Service Journal (2) Videos of PkM activities which can be accessed online; (3) Increasing the knowledge of the Hospital Marketing team through the Digital Marketing Hospital Transformation Strategy; (4) Integration of the results of PkM activities in the Hospital Marketing Management course; (6) Increasing students' skills in implementing the Digital Marketing Hospital Transformation Strategy in the Hospital Marketing Management course